2020
DOI: 10.1109/tmi.2020.2994459
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Classification and Localization of COVID-19 Markers in Point-of-Care Lung Ultrasound

Abstract: Deep learning (DL) has proved successful in medical imaging and, in the wake of the recent COVID-19 pandemic, some works have started to investigate DLbased solutions for the assisted diagnosis of lung diseases. While existing works focus on CT scans, this paper studies the application of DL techniques for the analysis of lung ultrasonography (LUS) images. Specifically, we present a novel fully-annotated dataset of LUS images collected from several Italian hospitals, with labels indicating the degree of diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
397
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(438 citation statements)
references
References 38 publications
1
397
0
5
Order By: Relevance
“…Computer-aided US diagnosis methods for breast cancer imaging have been researched, incorporating features relating to shape, margin, orientation, echo patterns and acoustic shadowing [10]. A more recent development has been reported to use deep learning techniques for extracting nonlinear features from US images at frame-level and videolevel using convex and linear probes with central frequency below 5 MHz [11]. Although this study demonstrated the feasibility of using deep learning to enable the characterisation of the state of high permeability and advanced disease, the issues of how to incorporate deep learning techniques into the US imaging chain from data acquisition to post image processing was ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Computer-aided US diagnosis methods for breast cancer imaging have been researched, incorporating features relating to shape, margin, orientation, echo patterns and acoustic shadowing [10]. A more recent development has been reported to use deep learning techniques for extracting nonlinear features from US images at frame-level and videolevel using convex and linear probes with central frequency below 5 MHz [11]. Although this study demonstrated the feasibility of using deep learning to enable the characterisation of the state of high permeability and advanced disease, the issues of how to incorporate deep learning techniques into the US imaging chain from data acquisition to post image processing was ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Lung ultrasound further carries the advantage of not imposing any radiation and eliminating the need for transferring the patient, since the examination can be performed bedside[ 21 ]. Roy et al[ 22 ] developed and tested several deep learning models for detection of COVID-19 associated patterns on lung ultrasound scans. Their models concurrently output the severity of lung disease on a 4-point scale and segmented the pathological area on each lung ultrasound scan.…”
Section: Initiativesmentioning
confidence: 99%
“…Their models concurrently output the severity of lung disease on a 4-point scale and segmented the pathological area on each lung ultrasound scan. Roy et al argue that their model could be beneficial in a point-of-care assessment of disease severity and also be used for triaging patients with COVID-19[ 22 ].…”
Section: Initiativesmentioning
confidence: 99%
“…Clinical interpretation of 2-D lung images is subjective, and at times, inaccurate, and irreproducible. Roy et al [68] developed a deep learning framework for classification and localization of COVID-19 markers in LUS. This framework derived from a spatial transformer network was able to predict the disease severity score associated with the input frame and provide localization of pathological artifacts in a weakly supervised manner.…”
Section: Potential Applications Of Ultrasound Elastography In Covmentioning
confidence: 99%